SISTEM PENDUKUNG KEPUTUSAN UNTUK PEMILIHAN PERUMAHAN TERBAIK DI ASAHAN MENGGUNAKAN ANALYTICAL HIERARCHY PR OCESS (AHP) - Yessica Siagian (Universitas Asahan, 2017)
Abstract - The rapid growth of housing in Asahan has actually caused business competition among unhealthy housing developers. Problems that often arise due to unfair competition between developers are developers trying to market their housing without taking into account the quality and legality of the housing to be built. The choice of housing can provide convenience to consumers in determining housing choices from the value of the comparison of each housing chosen by the community. The problem to be discussed in this study is how to choose the right housing using the Analytical Hierarchy Process (AHP) method. Keywords - SPK, Housing, Election